1996
DOI: 10.1007/s004670050157
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide in the developing kidney

Abstract: Although nitric oxide (NO) has a well-established role in regulating renal function in the adult, recent studies point to perhaps an even more critical role for NO in maintaining basal renal blood flow (RBF) and glomerular filtration rate (GFR) in the developing kidney. The immature kidney has enhanced renal hemodynamic and functional responses to stimulation and inhibition of NO synthesis when compared with the adult, and these increased responses are not mediated by prostaglandins. Increased intrarenal activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 83 publications
3
42
0
Order By: Relevance
“…These findings provided evidence that the role of NO in modulating renal vascular tone under physiological conditions predominates early in life. This age-dependent effect of L-NAME on RVR was confirmed in the present study and confirms previous observations in anesthetized newborn animals (34). In addition, we previously demonstrated age-dependent effects on renal vascular tone of intra-arterial administration of ACh (29), a muscarinic agonist known to elicit a vasodilation by producing NO.…”
Section: Discussionsupporting
confidence: 93%
“…These findings provided evidence that the role of NO in modulating renal vascular tone under physiological conditions predominates early in life. This age-dependent effect of L-NAME on RVR was confirmed in the present study and confirms previous observations in anesthetized newborn animals (34). In addition, we previously demonstrated age-dependent effects on renal vascular tone of intra-arterial administration of ACh (29), a muscarinic agonist known to elicit a vasodilation by producing NO.…”
Section: Discussionsupporting
confidence: 93%
“…It seems that nonselective NOS inhibition increases the oxygen costs of kidney function independently of ANG II and that kidney nNOS is responsible for these in vivo and in vitro effects. Solhaug et al (1996a) suggested that NO is vital in the developing kidney to maintain normal physiological function and to protect the immature kidney during pathophysiological stress. Springate et al (1997) noted that mouse renin genetransgenic rats had a blunted pressure-diuresis-natriuresis response that was corrected by inhibition of the renin-ANG system and suggested that their production of NO was normal.…”
Section: Other Vasculaturesmentioning
confidence: 99%
“…In the developing kidney, NO plays an important role in maintaining normal physiological function (Solhaug et al, 1996) and in regulating renal homodynamics . Maintenance of adequate NO is an additional mechanism for the preservation of vasculature in progressive renal diseases (Kang et al, 2002).…”
Section: Effects Of Subtotal (5/6) Nephrectomy On the Remaining Kidnementioning
confidence: 99%